PERLEMBAGAAN: ISU PERLAKSANAAN UNDANG-UNDANG ISLAM - Bahrom, Hasan (Jurnal Syariah, 2019)
This article attempts to discuss the importence of Article 3 alld 4 of Federal Constitution of Malaysia in cOlljuctioll with the implemelltation of Islamic laws in Malaysia. Are these articles really an obstacle to Islam or they are the way round? The author also tries hardly to interpret the meaning of "Islam is the religioll of Malaysia" by using golden interpretation in order to see Islamic law compatible and applicable to Malaysia.